2014
DOI: 10.1093/rheumatology/keu019
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant myocarditis and macrophage activation syndrome secondary to adult-onset Still’s disease successfully treated with tocilizumab

Abstract: IL-6 blockade in a case resistant to TNF neutralization should prompt a second diagnostic workup. Rheumatology key message. Neutralization of IL-6 by tocilizumab induces complete clinical remission and controls the growth of popliteal angiomatoid malignant fibrous histiocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 7 publications
(6 reference statements)
1
19
0
Order By: Relevance
“…Patient number 6 had fulminant myocarditis, but he continued to do well on TCZ as monotherapy after recovery from a cardiac arrest. Hence, TCZ was believed to be effective [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient number 6 had fulminant myocarditis, but he continued to do well on TCZ as monotherapy after recovery from a cardiac arrest. Hence, TCZ was believed to be effective [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigational drugs including NI-0501/anti-IFNγ monoclonal antibody and recombinant human IL-18 binding protein were discussed but ultimately were not included in the EBG because they were not FDA approved at the time of the workgroup meetings and thus were difficult to obtain outside of a clinical trial [31, 44]. Literature on the use of tocilizumab for HLH/MAS was reviewed by the EBG workgroup, including the impact of IL-6 on NK cell function [24, 25], rates of MAS in sJIA patients treated with tocilizumab [9, 50, 51], use of tocilizumab to treat MAS in sJIA and Adult-onset Still’s disease (AOSD) [52, 53], and efficacy of tocilizumab in cytokine release syndrome secondary to T cell engaging oncologic therapies [54, 55]. The reviewed phase III clinical studies demonstrated that MAS can occur in patients with sJIA while on tocilizumab, even with adequate sJIA disease control [9].…”
Section: Resultsmentioning
confidence: 99%
“…Studies regarding effective therapies are limited to case series and case reports. High dose corticosteroids with or without cyclosporine A was reported as first‐line therapy, followed by combinations with anakinra or tocilizumab as other options to improve clinical outcomes . IL‐1B is a proinflammatory cytokine, generated through cleavage of pro‐IL1B via the inflammasome, and plays a clear role in AOSD/MAS .…”
Section: Discussionmentioning
confidence: 99%